Workplace Reflection in the Age of AI: Materiality, Technology, and Machines. Issue 3 (August 2020) - Yorks, Lyle; Rotatori, Denise; Sung, SeoYoon; Justice, Sean
The Problem: This article explores the nature of reflection within the workplace during the fourth industrial revolution (4IR), a period characterized by the proliferation of cognitive technologies—like artificial intelligence (AI)—which are changing the nature of work. This piece explores the manner in which individuals and teams learn through reflective practice as a result of increased human–machine collaboration in the 4IR since it has not been extensively researched. The Solution: Through an analysis of Anand Rao's three-tiered model of AI— assisted intelligence, augmented intelligence, and autonomous intelligence— and by using data collected through a semi-structured interview process that situated the article within a particular sector of the economy—the health care industry—this article provides a framework for understanding the workplace, and human-machine collaboration, during the 4IR. The Stakeholders: Human resource development practitioners and researchers interested in the role of cognitive technologies within the workplace and their impact on human reflection.